SMART Intensive Care Unit (ICU) for better care and outcomes in hospital settings: A perspective on innovation - Septiani, Diah (Innovation in Health for Society, 2026)
The modernization of Intensive Care Units (ICUs) through digital transformation is essential for enhancing patient safety and optimizing clinical efficiency. This paper discusses the implementation of "SMART ICU" technologies designed to streamline nursing workflows and improve the precision of patient monitoring. Central to this innovation is the integration of hourly hemodynamic monitoring directly into the Electronic Medical Record (EMR) system. By automating data entry, the system minimizes human error, reduces the documentation burden on nursing staff, and provides real-time data visualization for rapid clinical decision-making. Furthermore, the SMART ICU framework introduces automated fluid balance calculations. By leveraging smart algorithms, the system automatically computes fluid status as soon as the patient's weight is updated, ensuring high accuracy in managing critically ill patients who are sensitive to fluid shifts. To support this, the integration of smart beds equipped with built-in weighing scales allows for frequent and non-invasive weight monitoring without the need for manual patient transfer. Together, these integrated features—automated hemodynamic tracking, digitized fluid management, and advanced hardware—create a seamless data ecosystem. Ultimately, the adoption of these SMART ICU technologies is expected to significantly improve clinical outcomes, reduce complications associated with manual monitoring, and allow healthcare providers to focus more on direct bedside patient care. Keywords: Better care, healthcare professional, innovation in health, Intensive Care Unit, mortality prevention